Gemblak stereotype film “kucumbu tubuh indahku” by Garin Nugroho - Oki, oki cahyo nugroho; Ridwan , Ridwan Yudha Pratama (Universitas Ahmad Dahlan, 2022)
Film is one of the electronic media that has a huge appeal among the public. Films also play an active role in conveying messages or information, but with very neat packaging. Make the message or information more interesting and entertain the audience. Based on this, many films always contain events or phenomena, one of which is the film